(untitled) (International Journal of Mathematics and Physics, 2024)
This manuscript presents an approach to accurately determine the orbits of Medium Earth Orbit (MEO) and Geosynchronous Earth Orbit (GEO) space objects by utilizing data from an electro-optical sensor (Optical Satellite Tracking Station (OSTS), Kottamia Observatory station). The proposed method combines an extended and unscented Kalman filter with a semi-analytical propagation model. The effectiveness of this approach is demonstrated through numerical simulations and comparisons with traditional orbit determination techniques. The results drawn from this study show that when comparing both methods, the unscented semi-analytical Kalman filter provided more accurate orbital state estimates and required less time and fewer observations to converge.